1983
DOI: 10.1002/ana.410140310
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of chemotherapeutic agents after blood‐brain barrier modification: Neuropathological studies

Abstract: We examined in 47 dogs the effects of 5-fluorouracil, Adriamycin (doxorubicin hydrochloride), cis-platinum (cis-diamminedichloroplatinum) cyclophosphamide, and bleomycin given in association with osmotic blood-brain barrier modification. The dose of drug ranged from 100% to as little as 5 to 10% of the conventional systemic dosage. Serial neurological observation and subsequent postmortem neuropathological evaluation at times varying from 2.5 hours to 52 days after drug administration showed that cis-platinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(40 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…On the basis of the previous publications [17,18,27,28] as well as the current study, it can be concluded that DXR and MXN are neurotoxic following bypass of the blood-brain-barrier. Our study indicates that a dose of 10% the LDo is almost always toxic in DXR treated animals and in MXN treated rats.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…On the basis of the previous publications [17,18,27,28] as well as the current study, it can be concluded that DXR and MXN are neurotoxic following bypass of the blood-brain-barrier. Our study indicates that a dose of 10% the LDo is almost always toxic in DXR treated animals and in MXN treated rats.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, it is not surprising that neurotoxicity has not been detected in the routine systemic use of these agents. However, neurotoxicity was observed after osmotic opening of the bloodbrain barrier in experimental animals treated with DXR [27,28]. Histopathological examination revealed necrosis and hemorrhagic infarction restricted to the areas of the barrier disruption [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDZ PSC 833). For instance, in animal experiments, the administration of various cytostatic drugs after the pharmacological opening of the blood-brain barrier led to severe functional and histological neurotoxicity (Neuwelt et al, 1983). Also in patients, increased local toxicity of chemotherapeutic agents has been observed by raising drug concentrations in the brain (Kaplan & Wiernik, 1982;Siegers, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Structural abnormalities of the endothelial lining, driven by an erratic angiogenesis, include open endothelial gaps (interendothelial junctions and transendothelial channels), cytoplasmic vesicles and fenestrations that contribute to leakiness and hyperpermeability of the tumor vasculature [17]. Circumvention of the BBB, although it increases drug concentrations in the tumor, also inevitably results in high concentrations of the cytotoxic drug in the normal brain -posing a threat of severe neurotoxicity [18]. Similarly, direct intervention into delicate brain structures often results in the loss of neurological and neurocognitive functions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%